Genotoxicity of gold nanoparticles in the gilthead seabream (Sparus aurata) after single exposure and combined with the pharmaceutical gemfibrozil. (April 2019) - Barreto, A.; Luis, L.G.; Pinto, E.; Almeida, A.; Paíga, P.; Santos, L.H.M.L.M.; Delerue-Matos, C.; Trindade, T.; Soares, A.M.V.M.; Hylland, K.; Loureiro, S.; Oliveira, M.
Abstract: Due to their diverse applications, gold nanoparticles (AuNPs) are expected to increase of in the environment, although few studies are available on their mode of action in aquatic organisms. The genotoxicity of AuNPs, alone or combined with the human pharmaceutical gemfibrozil (GEM), an environmental contaminant frequently detected in aquatic systems, including in marine ecosystems, was examined using gilthead seabream erythrocytes as a model system. Fish were exposed for 96 h to 4, 80 and 1600 μg L −1 of 40 nm AuNPs with two coatings – citrate or polyvinylpyrrolidone; GEM (150 μg L −1 ); and a combination of AuNPs and GEM (80 μg L −1 AuNPs + 150 μg L −1 GEM). AuNPs induced DNA damage and increased nuclear abnormalities levels, with coating showing an important role in the toxicity of AuNPs to fish. The combined exposures of AuNPs and GEM produced an antagonistic response, with observed toxic effects in the mixtures being lower than the predicted. The results raise concern about the safety of AuNPs and demonstrate interactions between them and other contaminants. Highlights: Gold nanoparticles (AuNPs) induced DNA damage in Sparus aurata at 4 μg.L −1 . Erythrocytic nuclear abnormalities (ENAs) increased after exposure to 4 μg.L −1 AuNPs. The induction of ENAs decreased with citrate coated AuNPs concentration increase. AuNPs combined exposures with gemfibrozil (GEM) induced DNA damage and ENAs. AuNPs and GEM combined exposures produced an antagonistic response.